Pretreatment and treatment with fructo-oligosaccharides attenuate intestinal mucositis induced by 5-FU in mice. (October 2018) - Galdino, Flávia Mendes Peradeles; Andrade, Maria Emília Rabelo; Barros, Patrícia Aparecida Vieira de; Generoso, Simone de Vasconcelos; Alvarez-Leite, Jacqueline Isaura; Almeida-Leite, Camila Megale de; Peluzio, Maria do Carmo Gouveia; Fernandes, Simone Odília Antunes; Cardoso, Valbert Nascimento
Graphical abstract: Abstract: Mucositis is a side effect observed in patients undergoing chemotherapy. Besides, this treatment also leads to the imbalance of the intestinal microbiota. This study evaluated the effects of pre and treatment with fructo-oligosaccharides (FOS) in intestinal mucositis induced by 5-fluorouracil (5-FU). Balb/c mice were divided into four groups: CTL (without mucositis + saline), MUC (mucositis + saline), PT (mucositis + 6% FOS before disease induction) and T (mucositis + 6% FOS after disease induction). Mucositis was induced with an intraperitoneal injection of 300 mg/kg 5-FU. After 72 h intestinal permeability (IP), inflammatory infiltrate, oxidative stress, histological analysis, and short-chain fatty acids (SCFA) production were evaluated. The MUC group showed lost weight, intense inflammatory infiltrate, increased oxidative stress and IP (P < 0.05). FOS supplementation attenuated all these parameters (P < 0.05). Only pretreatment was able to maintain the acetate and butyrate production. These results showed that FOS supplementation presented protective effects on intestinal barrier function.